Correlation of dynamic and static young’s modulus for limestone - Ailie Sofyiana Serasa; Abdul Ghani Rafek; Wan Salmi Wan Harun; Muslim Abdurrahman; Lee Khai Ern; Nguyen Xuan Huy; Tran Van Xuan; Rodeano Roslee; Mingwei Zhang; Goh Thian Lai (IOP Publishing, 2022)
The application of rock mechanics in the area of geotechnical engineering is important especially, in describing the strength of rock material for essessing the stability of excavations, foundations and slopes in rock. In this study, the characterization of the rock material was investigated through the Young’s modulus parameter, which describes the relationship between the stress applied to the rock material and the resulting strain. For an elastic and homogeneous solid, the measurement of Young’s modulus can be determined either from the static or dynamic measurements. Numerous studies outline the differences between the Young's modulus obtained from static and dynamic measurement in the laboratory. Comparatively, the measurement using static methods are more direct and realistic, as it describes the behaviour of rock deformation until failure occurs. The dynamic methods are more versatile and continuous, as they rely solely on the measurement of elastic wave velocities. However, one of the most notable disadvantages of rock material characterization by means of dynamic methods is that it overestimates the failure of rock material when compared to its actual value. With this in mind, the aim of this study is to obtain the measurements of Young’s modulus using both the static and dynamic methods. Based on the comparison made, an empirical equation of Est = 0.9264 (Edy) + 0.4976 with coefficient of determination, R2 of 0.8 is obtained for estimating the static Young’s modulus for limestone. The equation is applicable in situation where static measurement could not be carried out, and also serves as reliable estimation of Young’s modulus from dynamic measurement.